"A good consultation is a consultation where you didn't speak": HIV counselling as a denied and socially differentiated form of pedagogical authority. Issue 6 (2nd June 2020) - Gelly, Maud
ABSTRACT: AIDS-related death rates have dropped considerably since antiretroviral therapies became available in 1996, just as David Silverman was finishing his study of pre- and post-HIV test counselling. Twenty years later, HIV counselling is ripe for a revisit, in the tradition of sociological re-examination of health-care practices after a major therapeutic development has altered the stakes. The article is based on observations of 214 consultations prior to or following HIV testing that took place in France between 2012 and 2014. It demonstrates that HIV screening workers deny the pedagogical authority underlying their work, and analyses the conditions under which they vary their advice according to the social properties of the person being counselled.